2015
DOI: 10.3389/fpsyg.2015.01048
|View full text |Cite
|
Sign up to set email alerts
|

Metacognition-augmented cognitive remediation training reduces jumping to conclusions and overconfidence but not neurocognitive deficits in psychosis

Abstract: The majority of patients with schizophrenia display neurocognitive deficits (e.g., memory impairment) as well as inflated cognitive biases (e.g., jumping to conclusions). Both cognitive domains are implicated in the pathogenesis of the disorder and are known to compromise functional outcome. At present, there is a dearth of effective treatment options. A total of 90 patients with schizophrenia were recruited online (a diagnosis of schizophrenia had been confirmed in a large subgroup during a previous hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 60 publications
0
16
0
1
Order By: Relevance
“… Kanie et al (2014) reported that metacognition deficit in patients with schizophrenia includes decreased ability to evaluate the accuracy of one's own judgments, often due to overconfidence. Moritz et al (2015) also indicated that metacognition-augmented cognitive remediation therapy reduced overconfidence in patients with schizophrenia. The present results also suggested that metacognition was an important variable for evaluating the accuracy of one's own judgment.…”
Section: Discussionmentioning
confidence: 96%
“… Kanie et al (2014) reported that metacognition deficit in patients with schizophrenia includes decreased ability to evaluate the accuracy of one's own judgments, often due to overconfidence. Moritz et al (2015) also indicated that metacognition-augmented cognitive remediation therapy reduced overconfidence in patients with schizophrenia. The present results also suggested that metacognition was an important variable for evaluating the accuracy of one's own judgment.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, researchers examining the relationship between cognitive insight and neurocognition in people with schizophrenia found that poor performance on verbal learning assessments explained significant amounts of variance in overconfidence in responses, suggesting that overconfidence can be associated with poorer cognitive performance (Engh et al, 2011). Metacognitive awareness of errors in performance and overconfidence in performance when errors are made can also be linked to symptoms of the illness such as delusions (Moritz et al, 2006b; Moritz et al, 2006a), in that patients with delusions and hallucinations commonly manifest overconfidence (Bora et al, 2007) and that patients with higher levels of paranoia show increasing overconfidence when answering questions they consider to be easy (Moritz et al, 2015a, Moritz et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…While the determinants of challenges in self-assessment in schizophrenia are unknown, evidence points to potential neural underpinnings and a modulatory role of mood state. The increased confidence when incorrect seen in patients with schizophrenia may be based in their difficulties with self-monitoring, which may be associated with certain positive symptoms (Gawęda et al, 2013; Moritz et al, 2015a, Moritz et al, 2015b). Anatomical studies using neuroimaging have found that overconfidence in schizophrenia is related to hippocampal presubiculum atrophy, which is also implicates impairments in episodic memory (Orfei et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive flexibility is a mediating factor in improving symptomatology in cognitive and metacognitive therapies for psychosis (27,28). While it may also be subject to change (29)(30)(31), it is resistant to change by antipsychotic medication (32). Clarifying the facets of cognitive flexibility in psychosis and identifying different profiles of impairment may aid in developing tailored cognitive therapy programs but also to partially explain heterogeneity in psychosis.…”
Section: Introductionmentioning
confidence: 99%